Identification of marcasite in pyrite FeS2 thin films and the films' carrier transport characteristics. Issue 84 (26th August 2016) - Kim, Juran; Kim, Gee Yeong; Moon, Hankyoul; Yoon, Seokhyun; Seo, Il Wan; Lee, Yunsang; Moon, Dong Gwon; Ahn, SeJin; Jo, William
Abstract : 400 °C is optimal sulfurization temperature for pure pyrite FeS2 thin film, expecting better performance as light-absorber. Abstract : In this study, we characterized FeS2 thin films grown by the non-vacuum spin-coating method. We annealed the samples under a sulfur atmosphere at different sulfurization temperatures. The phase transformation from marcasite-containing pyrite to pure pyrite occurs between 350 and 400 °C. The structural phase formation on the films depends on the sulfurization temperature. It is known that pure pyrite thin films are more suitable for solar cells. FeS2 thin films with and without the marcasite phase were investigated in terms of their local electrical properties and carrier transport by conductive atomic force microscopy and Kelvin probe force microscopy. Interestingly, the pure pyrite thin film shows less conducting behavior than the mixed phase sample because the mixed phase thin film has other residues on the surface. Pure pyrite shows two major work functions at 4.64 and 4.70 eV, and the mixed phase sample has multiple surface potential peaks below 4.63 eV, which is the main pyrite FeS2 work function. Pure-phase pyrite thin films are promising for earth-abundant solar cell applications.